Self Directed Learning of Islamic Kidergarten Students in Improving Multiple Children's Intelligences - Waqi’atul Fadlilah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2018)
This study examines the efforts to improve the Multiple Intelligence of children through Self Directed Learning (SDL) in TK Inayah, Sidodadi, Paiton Probolinggo. In learning activities require high motivation and a supportive atmosphere in the learning process. For that learners need classroom of life in which there is a spirit of self-directed learning or self-learning so that the various talents that have children are expected to be exposed well. This research uses qualitative method of case study type by interviewing principal, teacher and ask directly to learners. The results show that Self Directed Learning (SDL) in this institution can improve Multiple Intelligence in children. They freely choose the space according to their talents and interests. Advisor only accompanies and directs according to the potential of the child.